2019
DOI: 10.1038/s41416-019-0637-9
|View full text |Cite
|
Sign up to set email alerts
|

ASCT2 (SLC1A5)-dependent glutamine uptake is involved in the progression of head and neck squamous cell carcinoma

Abstract: Background Glutamine is an abundant and versatile nutrient in cancer cells. Head and neck squamous cell carcinoma (HNSCC) was reported to be dependent on mainly glucose, not glutamine, for producing the energy required for survival and proliferation. Methods The roles of ASCT2 (SLC1A5) and associated glutamine metabolism were determined by the MTT, colony formation, glutamine uptake, intracellular glutathione, ROS detection, immunofluorescence, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 51 publications
(61 reference statements)
4
95
0
Order By: Relevance
“…Moreover, miR-137 exhibits crucial developmental roles in neuronal differentiation (57). In addition, miR-137, by modulating SLC1A5-dependent glutamine uptake, is involved in the progression of head and neck squamous cell carcinoma (58,59). The significant role of miR-137 in the progression, diagnosis and prognosis of hepatocellular carcinoma has also been documented (60).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, miR-137 exhibits crucial developmental roles in neuronal differentiation (57). In addition, miR-137, by modulating SLC1A5-dependent glutamine uptake, is involved in the progression of head and neck squamous cell carcinoma (58,59). The significant role of miR-137 in the progression, diagnosis and prognosis of hepatocellular carcinoma has also been documented (60).…”
Section: Discussionmentioning
confidence: 98%
“…While five members of this family (SLC1A1, SLC1A2, SLC1A3, SLC1A6, and SLC1A7) function as high-affinity Glu transporters, the remaining two (SLC1A4 and SLC1A5) work as neutral amino acid transporters [ 25 ]. In general, members of this family are essential for activation of the mTOR pathway to maintain cell growth and proliferation as reviewed in [ 26 ], and for coping with oxidative stress due to their contribution to the synthesis of GSH [ 27 , 28 , 29 ].…”
Section: Amino Acid Transporters Upregulated In Tumors and Their Rmentioning
confidence: 99%
“…V-9032 specifically and effectively targets SLC1A5 and thus leads to the attenuation of proliferation and growth of cancer cells as well as elevation of oxidative stress and cell death, contributing to anti-tumor responses both in vivo and in vitro [ 163 ]. Furthermore, either short hairpin RNA (shRNA) or miR-137-mediated silencing of SLC1A5 and pharmacological inhibition of SLC38A2 and SLC1A5 by V-9302 abolish intracellular Gln levels as well as Gln metabolism that eventually affects GSH production [ 29 ]. Overall, these effects lead to an increase in apoptosis, autophagy, and oxidative stress and suppression of the mTORC1 signaling and cell proliferation in HNSCC, further boosting tumor cell sensitivity to cetuximab treatment [ 29 ].…”
Section: Amino Acid Transporters As Targets For Tumor Treatmentmentioning
confidence: 99%
“…ASCT2, an Na + -dependent neutral amino acid transporter encoded by SLC1A5 , is predominantly localized at the cell membrane [ 35 ] and mediates the exchange of amino acid substrates, particularly mediating rapid glutamine uptake in proliferating cancer cells [ 36 ]. ASCT2 upregulation worsens the prognosis of HNSCC, clear-cell renal-cell carcinoma, gastric cancer, triple-negative breast cancer, ovarian cancer, and other cancers [ 37 , 38 ]. Kim et al [ 39 ] (2016) reported ASCT2 upregulation in MTC originating from parafollicular cells but not in other TCs of follicular origin, including PTC, FTC, poorly differentiated carcinoma, and ATC.…”
Section: Amino Acid Transporters and Thyroid Cancermentioning
confidence: 99%